Extraskeletal Ewing sarcoma arising from stomach and ovary: A case series of two rare sites - Singhal, Lalita; Tyagi, Vinod Kumar; Gupta, Rishi Kumar; Bhatnagar, Mohit (Indian Journal of Case Reports, 2024)
Ewing sarcoma is the second most common tumor in children and young adults. Primitive neuroectodermal tumors/Ewing sarcoma family consist of small round cell of neuroectodermal origin. Ewing sarcoma commonly arises from long bones and pelvic region but extraskeletal Ewing sarcoma (EES) is a very rare tumor with highly malignant potential associated with poor outcome. We present a case series of two cases, one is from the ovary in a 24-year-old young, married, multiparous woman who presented with metastatic disease and was treated with palliative chemotherapy. The second is an Ewing sarcoma arising from the stomach in a 33-year-old male who underwent surgery followed by adjuvant chemotherapy. EES is usually an uncommon tumor and many times, the diagnosis becomes delayed and presents with metastatic disease. Immunohistochemical and molecular analysis is a must to diagnose the EES. There are no standard treatment guidelines. Surgery, various chemotherapy regimens, and radiotherapy are given for treatment. Early diagnosis and interventions are required for better outcomes.